Apropiarse de la ciudad: clase media y memoria del desarrollo en Guia afetivo da perifería, de Marcus Vinícius Faustini (Altre Modernità, 2019)
In the novel Guia afetivo da periferia, by Brazilian author Marcus Vinicius Faustini, personal memory is used as a textual strategy to inscribe the subjectivity of the narrator's voice in an urban space marked by economic, social and political exclusion. This article discusses the different ways in which this use of memory can be read as a strategic resource to gain citizenship built from an economic discourse. Through narratives crossed by a rhetoric of social mobility, the narrative voice of the text displays an aspirational ethos that can be understood as a tactical understanding of a cultural policy of a given class. The inclusive possibilities of the culture to which this reading aims comment on the existence of the different ways in which the relations between periphery and literature should be thought in the current context of Brazil.